(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
This paper briefly summarizes the evaluation of the effects brought on by the devastating COVID-19 pandemic on public transport ridership. The transportation industry has been significantly impacted by COVID-19, thus this study identifies, analyses, and offers some useful improvement approaches to prevent the challenges that are currently occurring and being confronted, notably by stakeholders and the public. A questionnaire form was created, and with the aid of web based survey, a sample size of 180 survey forms was completed while taking into account D Morgan’s Table. Data and replies were gathered using the main data source. This is the initial study on the effects of COVID-19 on transportation in Srinagar (Jammu and Kashmir, India), and it is anticipated that it will be crucial in reducing the adverse effects of a pandemic on Srinagar’s transportation industry. In addition, the study emphasizes a number of significant elements that are very likely to affect travelers’ choices in the post-pandemic period. Factors such as respondents’ regular modes of transportation during the pre-COVID-19 period, their frequency of public transportation use in that time period, their anticipated change in trip frequency and virtual activities during the "new normal" situation, their perception of risk, and their confidence in preventive measures all had an impact on the anticipated change in frequency of travel by public transportation during that time period.